PENGARUH GAYA KEPEMIMPINAN TRANSFORMATIF TERHADAP PEMBENTUKAN KARAKTER DIMEDIASI DISIPLIN TARUNA AKMIL MAGELANG - Indriawati, Yulia; Mathori, Muhammad (Jurnal Riset Manajemen Akuntansi Indonesia, 2025)
This research aims to find out that the Transformative Leadership Style has a significant effect on the character formation of Military Academy Cadets, to find out that the Transformative Leadership Style has a significant effect on the discipline of Military Academy Cadets and to find out that the transformative leadership style has a significant effect on character formation mediated by the discipline of Magelang Military Academy Cadets. This research design uses quantitative research methods. The sample for this research was 93 Military Academy Cadets at levels II, III and IV. Data analysis uses convergent validity, average variance extracted (AVE), and discriminant validity tests, to test reliability it can be done through composite reliability and then using the smart model with PLS. The results of the research show the influence of Transformative Leadership Style on the character formation of Magelang Military Academy Cadets with a P-Value of 0.000 < 0.05 or with a t-statistic of 7,330 > 1.96, so Ho1 is rejected and Ha1 is accepted. There is an influence of the Transformative Leadership Style on the Discipline of the Magelang Military Academy Cadets with a P-Value of 0.000 < 0.05 or with a t-statistic of 18,345 > 1.96, so Ho2 is rejected and Ha2 is accepted. There is an influence of Cadet discipline on the formation of Cadet character which is mediated by the discipline of the Military Academy Cadets Magelang with a P-Value of 0.007 < 0.05 or with a t-statistic of 6,884 > 1.96, then Ho3 is rejected and Ha3 is accepted. There is an influence of the Transformative leadership style on the formation of Cadet character which is mediated by the discipline of the Magelang Military Academy Cadets with a P-Value of 0.000 < 0.05 or with a t-statistic of 7.926 > 1.96, so Ho4 is rejected and Ha4 is accepted.